2012
DOI: 10.1016/j.jiph.2011.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori genotypes can predict gastric tissue histopathology: A longitudinal study of Iranian patients

Abstract: This study showed that CagA-positive H. pylori infection is associated with more severe gastritis and with increased bacterial density and inflammation in the biopsy specimens. The 303-bp positive genotype was also significantly associated with higher grades of esophagitis. Additional in-depth trials will be helpful in extending our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The progress of disease seems to depend on bacterial genotypes, host and environmental factors. Some studies have reported a significant correlation between H. pylori genotypes and gastric histological damages [17-19]; whilst others reported a variability of genotypes distribution according to nationalities or geographical area [20]. To our knowledge, this is the first study conducted in North Africa and in Morocco on the association of H. pylori genotypes with gastric histological profiles.…”
Section: Discussionmentioning
confidence: 95%
“…The progress of disease seems to depend on bacterial genotypes, host and environmental factors. Some studies have reported a significant correlation between H. pylori genotypes and gastric histological damages [17-19]; whilst others reported a variability of genotypes distribution according to nationalities or geographical area [20]. To our knowledge, this is the first study conducted in North Africa and in Morocco on the association of H. pylori genotypes with gastric histological profiles.…”
Section: Discussionmentioning
confidence: 95%